2015
DOI: 10.1590/1982-0224-20140132
|View full text |Cite
|
Sign up to set email alerts
|

Gill dimensions in near-term embryos of Amazonian freshwater stingrays (Elasmobranchii: Potamotrygonidae) and their relationship to the lifestyle and habitat of neonatal pups

Abstract: This comparative study of gill morphometrics in near-term embryos of freshwater stingray potamotrygonids examines gill dimensions in relation to neonatal lifestyle and habitat. In embryos of the potamotrygonids Paratrygon aiereba, Plesiotrygon iwamae, Potamotrygon motoro, Potamotrygon orbignyi, and cururu ray Potamotrygon sp. the number and length of filaments, total gill surface area, mass-specific surface area, water-blood diffusion distance, and anatomical diffusion factor were analysed. In all potamotrygon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…The integration of all sensory systems in freshwater stingrays is indeed an important characteristic for the success of this group in a diversity of freshwater habitats, such as lakes, streams, shallow and deep waters such as beaches and river channels (Duncan et al 2015;Shibuya 2022). The synchronized performance of different sensory modalities plays an essential role in feeding behavior, with each sensory element having a primary function in different phases of foraging (search, location, and the phase prior to prey apprehension).…”
Section: Discussionmentioning
confidence: 99%
“…The integration of all sensory systems in freshwater stingrays is indeed an important characteristic for the success of this group in a diversity of freshwater habitats, such as lakes, streams, shallow and deep waters such as beaches and river channels (Duncan et al 2015;Shibuya 2022). The synchronized performance of different sensory modalities plays an essential role in feeding behavior, with each sensory element having a primary function in different phases of foraging (search, location, and the phase prior to prey apprehension).…”
Section: Discussionmentioning
confidence: 99%
“…The ventral bronchial skeleton consists of an enlarged central medial plate, which resulted from the fusion of the basibronchial copula and the basibronchial components (De Carvalho et al, 2004), a short and transversely directed basihyal, a pair of short and anteriorly directed hypobronchials, and five pairs of ceratobronchials. Duncan et al (2015) indicated to the gills are a multifunctional organ involved in gas exchange, acid-base, and ion regulation; where the structure and dimensions of gills of the potamotrygonid are important to assess their function. Gill measurements include gill filament's length and abundance, number of respiratory lamellae on the filaments, surface area of lamellar bilateral, total gill surface area, mass-specific gill area, and the water-blood diffusion barrier, are species-specific as reported from Hughes et al (1986).…”
Section: The Bronchial Skeletonmentioning
confidence: 99%
“…Charvet-Almeida em 2001, em trabalho sobre ocorrência, biologia e uso de raias de água doce na Baia de Marajó (Pará, Brasil), com ênfase na biologia de Plesiotrygon iwamae, constatou que todas as raias capturadas abortavam os embriões. O mesmo padrão de parto induzido por diferentes artes de pesca (espinhéis, arrasto e tarrafas) foi verificado por Duncan et al, (2015)…”
Section: Impactos Antrópicos E Ocorrência De Parto Induzido Por Pescaunclassified